Pelatihan Penerapan Model 5S Dalam Sistem Pengelolaan Sampah di Kampung Wisata Tobati, Kota Jayapura - Suriani Surbakti; Henderina J. Keiluhu; Yohana Yembise (LPPM Uncen, 2025)
Tobati Village is an area that has a buffer zone for water areas with the presence of mangrove forests, it is undeniable that with the changes and designation of land into tourist areas, the area has been polluted by waste. Therefore, this problem is important to be addressed with the aim of increasing the transportation capacity of Tobati Village through the design of a waste management system by adopting the 5S work attitude (Seiri, Seiton, Seiso, Seiketsu, and Shitsuke) which will emphasize the role of stakeholders in waste management. This community service aims to train the Tobati Village community in implementing an effective waste management system model by implementing the 5S work attitude. The community service method uses a qualitative and quantitative approach. This method aims to produce certain products and test the effectiveness of these products. The application was carried out in Tobati Village with 20 families as a sample of determination determined purposively. With this concept, it is hoped that waste that was previously produced as a pollutant will produce output that has economic value by utilizing waste that is still useful. The waste problem in the village will be solved by introducing a waste management model that has caused degradation and pollution of the Tobati village area. With the 5S Commitment to strengthening the ecological, social and economic roles of the community who have lived in the area for generations and live in peace and harmony with nature. Based on the discussion that has been carried out from the results of the community service, it can be concluded that most of the Tobati community stated that the 5S model was very effective in managing waste in the Tobati village and also There are many good impacts that arise if the rhepang area is used as an ecotourism object.